Pencegahan Pernikahan Anak (Dini) Sebagai Upaya Menanggulangi Stunting Di Desa Puledagel : Program Edukasi Dan Penyuluhan Gizi - Irchamni, Achmad; Gita Permatasari, Kristina; Puspitarani, Puspitarani; Yunitasari , Dinar (Blora International Journal of Community Engagement, 2025)
Child marriage is a social problem that has serious implications for maternal and child health, including growth retardation. Growth retardation due to malnutrition during the first 1000 days of life (HPW) can interfere with optimal growth and development in children. In Blora, one of the areas where the rate of child marriage is still high, the number of children with growth retardation is likely to increase. The purpose of this study was to determine the relationship between child marriage prevention and stunting prevention efforts through nutrition education and counselling programmes. The methodology used in this research is a qualitative approach involving community interviews and focus group discussions (FGDs) as well as providingcounselling on the impact of early marriage on the nutrition, growth, and development of children. This community service research is expected to foster awareness that counselling involving parents, community leaders, and prospective brides can increase understanding of the risks of child marriage and the importance of proper nutrition in child growth and development. Overall, prevention of child marriage through nutritional counselling support is expected to contribute significantly to reducing stunting rates in Puledagel village. This education programme aims to increase community awareness and create an environment that supports maternal and child health.